Economic Analysis of Para-wilt Management in Bt Cotton (Gossypium hirsutum L.) in Mansa District of South-western Punjab, India - Singh, Gurdeep; Singh, Pritpal; Singh, Kulwant; Sodhi, Gurjinder Pal Singh; Sekhon, Bhallan Singh (Indian Journal of Extension Education, 2021)
Parawilt characterized by a sudden drooping of leaves followed by death of plants within few hours after rainfall or heavy irrigation has been the major physiological disorder affecting productivity of Bt-Cotton (Gossypium hirsutum L.). We studied the effect of foliar application of cobalt chloride (@10 mg L-1 water) within 24-36 hours after appearance of symptoms on recovery rate, seed cotton yield and economics at farmersâ€™ fields in Mansa district of south-western Punjab. The results of front line demonstrations revealed that foliar application of cobalt chloride resulted in significantly (p<0.05) higher seed cotton yield by 9.1%, compared with the control (no-spray). The mean gross returns (MGRs) increased significantly by Rs. 9620/- ha-1 in the demonstration plots. The higher benefit-cost (B:C) ratio of 2.38 was observed for the demonstration plots, against 2.15 for the control (no-spray). The foliar application of cobalt chloride resulted in higher average production efficiency of Rs. 65.7 ha-1 d-1 and average economic efficiency of 1.1 kg seed cotton yield ha-1 d-1, compared with the control. These results therefore, revealed that farmers can effectively manage parawilt in Bt-cotton using foliar application of cobalt chloride and may increase seed cotton yield and economic returns.Â Â Â